2019
DOI: 10.30647/jip.v24i3.1314
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This research aims to determine the right strategy in developing ecotourism-based Pine Grenden Forest in Magelang City. This research uses descriptive method with a qualitative approach. Data collection is done by using observations, interviews, and questionnaires. This research using non probability sampling technique with a sample of 100 people in the Grenden Pine Forest. The sampling method in this study uses incidental sampling. Data collected were analyzed using SWOT analysis. The results of this study ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Previous studies observing the coastal area suggested Integrated Coastal Zone Management as the grand concept of development [27], particularly considering the multitude of potential and commodities (Figure 6) that could be utilized and managed for the tourism sector [28]. The research argues that tourism, especially ecotourism combined with aquaculture, appears to have economic potential for advancing development on the southern coast.…”
Section: Enhancing Economic Sectors To Address Development Challengesmentioning
confidence: 99%
“…Previous studies observing the coastal area suggested Integrated Coastal Zone Management as the grand concept of development [27], particularly considering the multitude of potential and commodities (Figure 6) that could be utilized and managed for the tourism sector [28]. The research argues that tourism, especially ecotourism combined with aquaculture, appears to have economic potential for advancing development on the southern coast.…”
Section: Enhancing Economic Sectors To Address Development Challengesmentioning
confidence: 99%
“…Pengawasan dilakukan secara langsung oleh pihak dinas karena dinas tetap memiliki tanggung jawab utama untuk mengelola dan mengawasi objek wisata Benteng Marlborough sesuai dengan tugas pokok dan fungsi dinas Pariwisata. Menurut penelitian Susanto & Kiswantoro (2020), fungsi terakhir dari peran tersebut, yaitu controlling, memerlukan dinas kebudayaan dan pariwisata untuk melakukan pemantauan dan evaluasi setiap bulan terhadap pengelolaan. Pengawasan yang dilakukan oleh pihak dinas Pariwisata Bengkulu terkait dengan wisata sejarah Benteng Marlborough pengelolaan objek wisata Benteng Marlborough telah dilakukan dengan baik oleh beberapa pihak yang berwenang, termasuk pemerintah provinsi dan pemerintah pusat.…”
Section: Controlling (Pengawasan)unclassified